2008
DOI: 10.1007/s10509-008-9893-5
|View full text |Cite
|
Sign up to set email alerts
|

Zel’dovich Λ and Weinberg’s relation: an explanation for the cosmological coincidences

Abstract: In 1937 Dirac proposed the large number hypothesis (LNH). The idea was to explain that these numbers were large because the Universe is old. A time variation of certain "constants" was assumed. So far, no experimental evidence has significantly supported this time variation. Here we present a simplified cosmological model. We propose a new cosmological system of units, including a cosmological Planck's constant that "absorbs" the well known large number 10 120 . With this new Planck's constant no large numbers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…The square root of this value corresponds approximately to the ratio of the size of proton and Plancks length. The cubic of the last mentioned ratio (about 10 61 ) corresponds roughly to the order of magnitude of the ratio between the age of universe and Plancks time [14].…”
mentioning
confidence: 80%
“…The square root of this value corresponds approximately to the ratio of the size of proton and Plancks length. The cubic of the last mentioned ratio (about 10 61 ) corresponds roughly to the order of magnitude of the ratio between the age of universe and Plancks time [14].…”
mentioning
confidence: 80%
“…Note that an incomplete form of relation (8) (9) was known to Dirac [7] and Weinberg [8], but there are problems with relation (9). In fact, we are forced to choose 0 H H = in relation (9) and even so the left-hand side is about one order of magnitude greater than the right one.…”
mentioning
confidence: 99%
“…In fact, we are forced to choose 0 H H = in relation (9) and even so the left-hand side is about one order of magnitude greater than the right one. In order to save the general form of relation (9) Dirac has suggested that ratio G H stays constant with time; hence introducing a varying gravitational "constant".…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The first of these by Hajdukovic (2010) is yet another exploration of the rich world of "cosmic coincidences" which are often described under the general heading of the Dirac large number hypothesis (Dirac 1938), but whose intellectual origins go back to Weyl a couple of decades earlier. Many such "coincidences" have now been investigated and discussed in the pages of this journal, most recently by Dinculescu (2009), Alfonso-Faus (2008 and Sorrell (2008). These attack the problem from a number of different viewpoints and working hypotheses, but involve similar expressions connecting fundamental atomic constants with cosmological quantities such as the Hubble Constant, the Black-Body temperature of the Universe and the Cosmological Constant.…”
mentioning
confidence: 99%